2015
DOI: 10.3892/or.2015.3898
|View full text |Cite
|
Sign up to set email alerts
|

IL-33-induced JNK pathway activation confers gastric cancer chemotherapy resistance

Abstract: Abstract. Inflammation is regarded as one of the major hallmarks of tumors, and has a very close relationship with gastric cancer. Interleukin-33 (IL-33), a new member of the IL-1 family, plays an important role in both inflammatory disease and tumors. The present study was designed to explore the effects of IL-33 on the proliferation, drug sensitivity, and the invasiveness of gastric cancer cells in vitro. IL-33 at concentrations lower than 100 pg/ml did not alter the inhibitory rate of gastric cancer cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…In addition to cytoreductive surgery, cisplatin-based chemotherapy is one of the most important therapeutic strategies for ovarian cancer (2). Previous studies have shown that Wnt signaling pathway deregulation correlates with ovarian cancer cell proliferation, survival, invasion and metastasis (25,26,28,30,31). Furthermore, cisplatin chemoresistance has been an obstacle in the successful treatment of ovarian cancer (8,32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cytoreductive surgery, cisplatin-based chemotherapy is one of the most important therapeutic strategies for ovarian cancer (2). Previous studies have shown that Wnt signaling pathway deregulation correlates with ovarian cancer cell proliferation, survival, invasion and metastasis (25,26,28,30,31). Furthermore, cisplatin chemoresistance has been an obstacle in the successful treatment of ovarian cancer (8,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that aberrant Wnt/JNK signaling may initiate and stimulate the development of malignant phenotypes through effects on cell proliferation, survival, polarity, invasion and metastasis (Fig. 1C) (29,30). …”
Section: Introductionmentioning
confidence: 93%
“…Once JNK activity is inhibited, 5‐FU‐ and GEM increase intracellular ROS production and thereby promote the apoptosis of CSCs . JNK activation increases the expression of ST2 (an interleukin (IL)−33 reporter) in gastric cancer cells, making them resistant to platinum‐based chemotherapeutics . JNK1 inhibition sensitizes HT29 colon adenocarcinoma cells to oxaliplatin .…”
Section: Jnk Signaling Plays a Role In Cancer Chemoresistancementioning
confidence: 99%
“…IL‐33 overexpressed in GC (Sun et al, ), stimulated the production of MMP‐3 and IL‐6 through activating ST2–ERK1/2 pathway, resulting in enhancement of cell invasion and migration (Yu et al, ). Ye et al () demonstrated that IL‐33 inhibited GC cell apoptosis induced by chemical compounds containing platinum via the ST2‐JNK axis and enhanced cell invasion through activating the JNK pathway. Therefore, the level of IL‐33 should be considered during the chemotherapy of GC.…”
Section: Action Of Other Cytokines In Gcmentioning
confidence: 99%